Obesity associated Lyplal1 gene is regulated in diet induced obesity but not required for adipocyte differentiation. (15th August 2015) - Lei, Xinnuo; Callaway, Mayson; Zhou, Hongyi; Yang, Yi; Chen, Weiqin
Highlights: Lyplal1 is highly expressed in murine adipose tissues. Lyplal1 expression in gonadal fat is markedly reduced in diet induced obesity. Adipose Lyplal1 expression demonstrates sexual dimorphism. Lyplal1 is upregulated during adipocyte differentiation independent of PPARγ. Lyplal1 is not essential for adipocyte differentiation and insulin action. Abstract: Obesity and its associated morbidities represent one of the major and most rapidly expanding health epidemics in the world. Recent genome-wide association studies (GWAS) have identified several variants in LYPLAL1 gene that are significantly associated with central obesity preferentially in females. However, the exact function of this gene in adipose tissue development and obesity remains completely uncharacterized. We found murine Lyplal1 gene demonstrated a depot and sex-specific expression profile in white adipose tissues (WAT), and was significantly reduced in the epididymal and retroperitoneal fats in a murine model of high fat diet induced obesity (DIO). Lyplal1 mRNA was mildly up-regulated during adipogenesis and enriched in mature adipocytes through a PPARγ-independent mechanism. However, overexpression and knockdown of Lyplal1 did not significantly perturb adipocyte differentiation, triacylglycerol accumulation and/or insulin signaling. These data highlight a depot-specific marked reduction of Lyplal1 transcripts in diet induced obesity but a dispensable role of Lyplal1 in adipose tissue development.